Design, synthesis, and insecticidal activities of propargyloxy-naphthalene-sulfonamide derivatives. Issue 4 (3rd April 2022) - Zhao, Wang-Yu; Yang, Chao-Fu; Han, Li-Juan; Zhou, Bo; Li, Ai-Juan; Liu, Lu-Lu; Zhang, Zi-Wei; Wang, Zi-Yu; Wu, Wen-Jun; Zhang, Ji-Wen
Abstract: In our previous studies, a kind of novel benzenesulfonamides was found to be a candidate insecticidal compounds. It was shown that propargyloxy and sulfonamide groups are pharmacodynamic groups. One hundred and twenty-six (126) naphthalenesulfonamides derivatives with propargyloxy functionality were designed and synthesized, and their insecticidal activities were determined. Some of them showed outstanding activity, with LC50 values as low as 0.202 mg ml −1, much lower than that of the positive control celangulin V (23.9 mg ml −1 ). In addition, the structure–activity relationships were discussed, and molecular docking was used to verify the binding mode of the compound and the target receptor. Graphical abstract: UF0001